Empathy and Humility as Predictors of Forgiveness Towards One’s Partner and Relationship Satisfaction in Young Adults - Fupšová, Tatiana; Záhorcová, Lucia (Studia Psychologica, 2022)
The study examines whether empathy and humility (both as individual characteristics and partner’s perceived characteristics) are predictors of forgiveness towards one’s partner and relationship satisfaction in young adults. The sample consisted of 226 young adults. Hierarchical regression analysis showed that conditions for forgiveness explained 7.6% of the variance in forgiveness toward one’s partner, while empathy and humility explained an additional 13.6% of that variance. The individual’s perspective-taking and their partner’s perceived empathy relate to positively predicted forgiveness towards one’s partner, and perceived partner’s superiority relates negatively. The multiple regression analysis showed that empathy, humility, and forgiveness towards one’s partner explain 43.4% of the variance in relationship satisfaction. The strongest negative predictor of relationship satisfaction was partner superiority and the strongest positive predictor was forgiveness towards one’s partner. Forgiveness towards one’s partner and partner’s perceived empathy and humility seem to play an important role in relationship satisfaction.